2020
DOI: 10.1016/j.ebiom.2020.102915
|View full text |Cite
|
Sign up to set email alerts
|

Serologic responses to SARS-CoV-2 infection among hospital staff with mild disease in eastern France

Abstract: Background The serologic response of individuals with mild forms of SARS-CoV-2 infection is poorly characterized. Methods Hospital staff who had recovered from mild forms of PCR-confirmed SARS-CoV-2 infection were tested for anti-SARS-CoV-2 antibodies using two assays: a rapid immunodiagnostic test (99.4% specificity) and the S-Flow assay (~99% specificity). The neutralizing activity of the sera was tested with a pseudovirus-based assay. Findings … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
105
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 100 publications
(116 citation statements)
references
References 31 publications
9
105
2
Order By: Relevance
“…However, early serology sampling does not explain the relative lack of agreement with COVID-19 diagnosis for Euroimmun IgG (19/21), Abbott IgG (16/21), Wantai Ab (19/21), and DiaPro IgG confirmation assay (20/21) in routine care setting. Similar observations have been made in populations of healthcare professionals, with false negative rates ranging from 1 % [ 27 ] to 20 % [ [28] , [29] , [30] ] several weeks after disease. This could be due to the high proportion of patients with mild COVID-19, resulting in low rates of seroconversion [ 28 ].…”
Section: Discussionsupporting
confidence: 75%
“…However, early serology sampling does not explain the relative lack of agreement with COVID-19 diagnosis for Euroimmun IgG (19/21), Abbott IgG (16/21), Wantai Ab (19/21), and DiaPro IgG confirmation assay (20/21) in routine care setting. Similar observations have been made in populations of healthcare professionals, with false negative rates ranging from 1 % [ 27 ] to 20 % [ [28] , [29] , [30] ] several weeks after disease. This could be due to the high proportion of patients with mild COVID-19, resulting in low rates of seroconversion [ 28 ].…”
Section: Discussionsupporting
confidence: 75%
“…As other groups, we report that COVID-19 patients generate variable levels of NAbs that reach a plateau 2 weeks postsymptom onset (Fafi-Kremer et al, 2020;Liu et al, 2020;Ni et al, 2020;Robbiani et al, 2020;Wölfel et al, 2020;Wu et al, 2020a). Our results also indicate that the SARS-CoV-2 does not induce a prolonged NAb response since we observed a drop of the NAb titer for several patients a few weeks after infection.…”
Section: Discussionsupporting
confidence: 68%
“…The short time frame of the sampling also allowed us to compare the performance of the four different serological assays at a given date and within a limited geographical region. We recently reported that among a cohort of 160 hospital staff in Strasbourg (France) with mild symptoms who were all positive by RT-qPCR for SARS-CoV-2 infection, a rapid immunodiagnostic commercial test detected antibodies in 153 (95.6%) of these samples and the S-Flow assay detected antibodies in 159 (99.4%) of these samples ( 26 ). The sensitivity of the S-Flow assay is thus >99%.…”
Section: Discussionmentioning
confidence: 99%